The Impact of Policy on Community Economic Growth - Marjono Marjono (Paspama Institute, 2025)
Economic policy plays an important role in promoting growth and equitable distribution of welfare among the people. This study aims to analyze the impact of fiscal, monetary, and economic development policies on Indonesia's economic growth. Using qualitative descriptive methods, secondary data were collected from academic literature, government reports, and publications from international organizations. The results of the analysis show that fiscal policies, such as energy subsidies and incentives for MSMEs, contribute to maintaining purchasing power and encouraging economic activity in the informal and agricultural sectors. On the other hand, appropriate monetary policies, including inflation control and interest rate adjustments, also strengthen macroeconomic stability and investment. Meanwhile, economic development policies that focus on infrastructure equity and job creation have succeeded in reducing regional inequality and poverty. The combination of these three policies has proven effective in accelerating economic recovery after the COVID-19 pandemic, as indicated by GDP growth, a decline in unemployment, and improvements in the Gini ratio and HDI. These findings emphasize the importance of synergy between adaptive policies and cross-sector collaboration in responding to global economic dynamics.